Isolated Feet Edema in Turner Syndrome by Prenatal Ultrasonography – Case Report and Literature Review - Ma J; Liang L; Liu S; Yan K; Zhang L (International Journal of Women's Health)
Jing Ma,* Li Liang,* Shanshan Liu, Kailin Yan, Li Zhang Department of Ultrasound Medicine, Tangdu Hospital, Air Force Medical University, Xi’an, People’s Republic of China*These authors contributed equally to this workCorrespondence: Li Zhang, Department of Ultrasound Medicine, Tangdu Hospital, 569# Xinsi Road, Baqiao District, Xi’an, People’s Republic of China, Email lilyzhang319_20@hotmail.comPurpose: Turner syndrome (TS), also known as congenital ovarian hypoplasia syndrome, is a sex chromosome abnormality caused by a complete/partial absence of the second sex chromosome with complete X chromosome. The most common findings by prenatal ultrasonography of TS include thickened nuchal translucency, cystic hygroma, cardiovascular system abnormalities, urinary system diseases, and growth retardation.Case Presentation: We present a unique case of TS with the ultrasonographic features of dorsal skin edema on both feet and a progressive slow growth of humerus length (HL) and femur length (FL) at the second trimester of spontaneous pregnancy. We performed an extensive review of prenatal ultrasound features of TS cases from MEDLINE (PUBMED) published in English between 2000 and 2024 to prove this case’s uniqueness. A 29-year-old pregnant woman with her second pregnancy after a previous missed abortion presented as the prenatal ultrasound exam for fetal structural anomalies at 24+3 weeks gestation revealed an edema of the dorsal skin on both feet and a short long bone of both femur and humerus for gestational age. Nuchal translucency (NT) measurement at week 13+6 was 1.3mm, and fetal echocardiography at week 24+2 showed normal. There were no markedly abnormal findings in the results of non-invasive prenatal test (NIPT) cell-free fetal DNA (cff-DNA) at 14+6 weeks. Then, amniocentesis was performed and the results confirmed Turner syndrome with a 45,X karyotype. The final review included 11 with a total number of 884 cases identified, among which central lymphedema such as increased nuchal translucency or cystic hygroma is the typical finding with TS by ultrasonographic examination. Peripheral lymphedema resulting in fetal substantial swelling in feet was reported in 3 cases. Fetal feet edema accompanied with growth retardation are extremely rare.Conclusion: Peripheral lymphedema such as feet edema accompanied with long bone-involved growth retardation is rare but recognized features by prenatal ultrasonography, which should be considered as an index of chromosomal abnormalities in fetus with TS.Keywords: Turner syndrome, ultrasonography, prenatal, edema, karyotype